2017
DOI: 10.1101/113597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exact sequence variants should replace operational taxonomic units in marker gene data analysis

Abstract: Recent advances have made it possible to analyze high-throughput marker-gene sequencing data without resorting to the customary construction of molecular operational taxonomic units (OTUs): clusters of sequencing reads that differ by less than a fixed dissimilarity threshold. New methods control errors sufficiently that sequence variants (SVs) can be resolved exactly, down to the level of single-nucleotide differences over the sequenced gene region. The benefits of finer taxonomic resolution are immediately ap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
740
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(751 citation statements)
references
References 16 publications
(18 reference statements)
7
740
0
4
Order By: Relevance
“…Our second focus here was on refining the replicated associations with new methods that resolve exact sequence variants from amplicon data, rather than lumping sequences within an arbitrary dissimilarity threshold into operational taxonomic units (OTUs) (30). This high-resolution approach localized all of the risk associated with the Gardnerella genus to a subspecies clade, and differentiated N. gonorrhoeae from other Neisseria species within 3% Hamming distance over the sequenced gene region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our second focus here was on refining the replicated associations with new methods that resolve exact sequence variants from amplicon data, rather than lumping sequences within an arbitrary dissimilarity threshold into operational taxonomic units (OTUs) (30). This high-resolution approach localized all of the risk associated with the Gardnerella genus to a subspecies clade, and differentiated N. gonorrhoeae from other Neisseria species within 3% Hamming distance over the sequenced gene region.…”
Section: Discussionmentioning
confidence: 99%
“…DADA2 was used to infer the amplicon sequence variants (ASVs) present in each sample (39). Exact sequence variants provide a more accurate and reproducible description of amplicon-sequenced communities than is possible with OTUs defined at a constant level (97% or other) of sequence similarity (30). See SI Materials and Methods for details.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors proposed that denoising should be performed before clustering to identify genuine sequence variants, using different procedures, such as the UNOISE2 algorithm that we have adapted here (Edgar 2016), the MED (minimum entropy decomposition; Eren et al 2015) procedure, or the DADA2 algorithm (divisive amplicon denoising algorithm; Callahan et al 2016). It has also been suggested that sequence variants should replace MOTUs to capture relevant biological variation (Edgar 2016, Callahan et al 2017. This suggestion may be adequate in prokaryotes, where strains of the same species can have different characteristics (e.g., pathogenicity).…”
Section: Discussionmentioning
confidence: 99%
“…Quality filtering and clustering into ESVs (Callahan et al 2017) was done with a customized pipeline largely based on UPARSE (Edgar 2013) implemented in USEARCH v.8 (Edgar 2010). Pair-end reads were merged using the USEARCH fastq_mergepairs algorithm (Edgar and Flyvbjerg 2015) with a required overlap of at least 30 base pairs and a minimum length of the merged sequence of 150 bp.…”
Section: Sequence Quality Filtering Exact Sequence Variant (Esv) Clumentioning
confidence: 99%